Measurement of singlet oxygen generation of 9(Hydroxymethyl)anthracene substituted silicon phthalocyanine by sono-photochemical and photochemical studies - Atmaca, Goknur Yasa (ELSEVIER, 2021)
Sono-photochemical study which combines photochemical and sonochemical studies is a favorable alternative modality to produce high singlet oxygen. However, though there are many articles about the calculation of singlet oxygen quantum yield for Photodynamic therapy (PDT) studies in the literature, there is no study to measure the efficiency of singlet oxygen for Sono-photodynamic therapy (SPDT) method. Therefore, this study aimed to synthesis a complex with improved photochemical properties and then calculates the efficiency of singlet oxygen by both of photochemical and sono-photochemical studies in DMSO and DMF. The designed complex showed remarkably high singlet oxygen quantum yields. The Phi(Delta) values (0.74 in DMSO, 0.72 in DMF for photochemical study) reached to 0.96 in DMSO, 0.88 in DMF for sono-photochemical study and these results prove that SPDT improves the therapeutic activity due to the sono-photochemical effect. This article will lead to the studies that seek to obtain highly efficient singlet oxygen. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Sono-photochemical; Photochemical; Phthalocyanine; Singlet oxygen; PHOTODYNAMIC THERAPY; CANCER; ZINC; DERIVATIVES; Chemistry